Ti(C,N) based metal ceramic tool material and preparation method thereof

By adding W-La composites to the Ti(C,N)-based cermet tool material and adopting cold isostatic press forming and sintering processes, the problem of easy cracking and cutting edge damage in cutting applications is solved, which significantly improves its bending strength and toughness and expands the application range.

CN119332148BActive Publication Date: 2025-04-08HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411899926.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Ti(C,N)-based cermet tool materials are prone to cracking and blade damage in cutting applications, resulting in limited application range.

Method used

Ti(C,N)-based cermet tool material including components of TiN, WC, Co, C, Ta, W-La2O3 and TiC is used, and is dissolved into the core-ring structure of the material through the form of a W-La composite, and a high-strength and hardness tool material is prepared in combination with cold isostatic press forming and sintering processes.

Benefits of technology

Through the solid solution and preparation process of W-La composite, the comprehensive performance of Ti(C,N)-based metal cermet tools is significantly improved, the bending strength and toughness are enhanced, the cracking and blade damage is reduced, and its application range is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332148B_ABST
    Figure CN119332148B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of metal tool processing, in particular to a Ti(C, N)-based cermet tool material and a preparation method thereof, wherein a Ti(C, N)-based cermet tool material is disclosed, comprising components in the following weight ratios: 8wt.% TiN, 15wt.% WC, 15wt.% Co, 1wt.% C, 4wt.% Ta, 0wt.% to 4wt.% W-10wt.%, and 53wt.% to 57wt.% TiC. The present invention solid-dissolves the W-La complex into the core-ring structure of the Ti(C, N)-based cermet, thereby strengthening and purifying the grain boundaries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal tool processing, and in particular to a Ti(C, N)-based metal ceramic tool material and a preparation method thereof. Background Art

[0002] Martensitic stainless steel is a typical high-strength steel with high hardness and high viscosity, which is easy to cause failure forms such as tool adhesion and diffusion wear, resulting in high processing costs. The selection of high-performance tool materials can reduce the adhesion and diffusion wear of tools during processing. Therefore, Ti (C, N)-based cermets have been studied as a high-strength steel substitute in the field of cutting processing. Compared with WC-Co cemented carbide containing rare elements W and Co, Ti (C, N)-based cermets are relatively cheaper and have more abundant resources, with obvious economic advantages. From the performance point of view, Ti (C, N)-based cermets have lower density, higher strength and hardness, but Ti (C, N)-based cermets have a relatively brittle structure. Although they have high strength, they are often found to break in various cutting applications, and the blade is easily damaged, which limits their application range. Summary of the invention

[0003] The present invention aims at the deficiencies in the prior art and provides the following technical solutions:

[0004] Ti(C,N) based cermet tool material, comprising components in the following weight ratios:

[0005] 8wt.%TiN;

[0006] 15wt.% WC;

[0007] 15wt.% Co;

[0008] 1wt.%C;

[0009] 4wt.%Ta;

[0010] 0wt.%~4wt.%W-10wt.%La2O3;

[0011] 53wt.%~57wt.% TiC.

[0012] As an improvement of the above technical solution, the particle size of the TiN powder is 0.1~2.0 microns, the particle size of the WC powder is 0.1~1.56 microns, the particle size of the Co powder is 1.0~10.0 microns, the particle size of the C powder is 0.1~2.7 microns, the particle size of the Ta powder is 0.1~4.5 microns, and the particle size of the TiC powder is 0.1~4.5 microns.

[0013] The preparation method of Ti(C,N) based metal ceramic tool material comprises the following steps:

[0014] S10: W and La are converted into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and the corresponding mass of ammonium paratungstate and lanthanum nitrate are weighed for pretreatment to obtain a W-10wt.%La2O3 composite powder.

[0015] S20: Weigh the components of the Ti(C,N)-based metal ceramic tool material according to the above scheme in various weight ratios, mix the raw materials and perform ball milling to obtain a mixed powder.

[0016] S30: cold isostatic pressing the mixed powder to obtain a Ti(C,N)-based metal ceramic blank, and sintering the blank to obtain the machinable high-strength steel Ti(C,N)-based metal ceramic tool material as described in the above scheme.

[0017] As an improvement of the above technical solution, step S10 includes the following steps:

[0018] S11: convert W and La into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and weigh the corresponding mass of ammonium paratungstate and lanthanum nitrate.

[0019] S12: Dissolve ammonium paratungstate and lanthanum nitrate respectively with deionized water, and place the dissolved solutions in a magnetic stirrer for stirring and mixing, and dry them in a vacuum blower oven after sufficient reaction to obtain a precursor powder.

[0020] S13: Grind the precursor powder with an agate mortar and keep it warm in an argon tube furnace to obtain a mixed oxide containing rare earth oxide and tungsten oxide, and place the oxide in a vacuum tube sintering furnace for reduction, and cool it to room temperature in a hydrogen environment to obtain a W-10wt.%La2O3 composite powder.

[0021] As an improvement of the above technical solution, the drying temperature of the vacuum blast oven in step S12 is 60~80°C, and the drying time is 2~4h. The argon protection temperature of the tubular furnace in step S13 is 450~500°C, and the insulation time is 1~3h. The hydrogen reduced in the vacuum tubular sintering furnace is high-purity hydrogen, the reduction temperature is 800~950°C, the heating rate is 5°C / min, and the reduction time is 6~10h.

[0022] As an improvement of the above technical solution, the ball-to-material mass ratio of the ball milling treatment in step S20 is 8:1, the ball mill speed is 200 r / min, and the ball milling mixing time is 24 h.

[0023] As an improvement of the above technical solution, after the step S20 is executed, the obtained mixed powder is dried.

[0024] As an improvement of the above technical solution, the pressure of the cold isostatic pressing process in step S30 is 180 MPa, the holding time is 3 min, the sintering temperature in the sintering process is 1430 degrees Celsius, and the sintering time is 60 min.

[0025] As an improvement of the above technical solution, the following steps need to be performed before the cold isostatic pressing process:

[0026] S21: adding paraffin wax to the mixed powder for mixing and granulating the mixture to facilitate cold isostatic pressing.

[0027] Beneficial effects of the present invention:

[0028] The present invention dissolves W-La into the core-ring structure of Ti(C,N)-based cermet in the form of a W-La complex, which plays a role in strengthening and purifying the grain boundaries. Furthermore, the W-La composite powder is prepared by a wet chemical method, which can ensure that La is evenly distributed in the W matrix, thereby making the La atoms more evenly distributed in the core-ring structure, further enhancing the overall comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the microstructure diagram of Test Example 1 of the present invention;

[0030] Figure 2 This is the Ti(C,N) based metal ceramic tool of test example 1 of the present invention;

[0031] Figure 3 The cutting chips are the martensitic stainless steel cutting chips of Test Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0033] Compared with WC-Co cemented carbide containing rare elements W and Co, Ti(C,N)-based cermets are relatively cheaper and more abundant in resources, and have obvious economic advantages. From the performance point of view, Ti(C,N)-based cermets have lower density, higher strength and hardness, but the Ti(C,N)-based cermets themselves have a relatively brittle structure. Although they have high strength, chipping is often found in various cutting applications, and the blade is easily damaged, which limits its application range.

[0034] In order to solve the above problems, the following embodiments are provided: Embodiment 1

[0035] Provided is a Ti(C,N)-based cermet tool material comprising components in the following weight ratios:

[0036] 8wt.% TiN; 15wt.% WC; 15wt.% Co; 1wt.% C; 4wt.% Ta; 0wt.%~0.4wt.% W-10wt.% La2O3; 53wt.%~57wt.% TiC.

[0037] As an improvement of the above technical solution, the particle size of the TiN powder is 0.1~2.0 microns, the particle size of the WC powder is 0.1~1.56 microns, the particle size of the Co powder is 1.0~10.0 microns, the particle size of the C powder is 0.1~2.7 microns, the particle size of the Ta powder is 0.1~4.5 microns, and the particle size of the TiC powder is 0.1~4.5 microns. Embodiment 2

[0038] In order to cooperate with the first embodiment, a method for preparing a Ti(C,N)-based metal ceramic tool material is also provided, comprising the following steps:

[0039] S10: W and La are converted into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and the corresponding mass of ammonium paratungstate and lanthanum nitrate are weighed for pretreatment to obtain a W-10wt.%La2O3 composite powder.

[0040] The step S10 comprises the following steps:

[0041] S11: convert W and La into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and weigh the corresponding mass of ammonium paratungstate and lanthanum nitrate.

[0042] S12: Dissolve ammonium paratungstate and lanthanum nitrate respectively with deionized water, and place the dissolved solutions in a magnetic stirrer for stirring and mixing, and dry them in a vacuum blower oven after sufficient reaction to obtain a precursor powder.

[0043] S13: Grind the precursor powder with an agate mortar and keep it warm in an argon tube furnace to obtain a mixed oxide containing rare earth oxide and tungsten oxide, and place the oxide in a vacuum tube sintering furnace for reduction, and cool it to room temperature in a hydrogen environment to obtain a W-10wt.%La2O3 composite powder.

[0044] Among them, the drying temperature of the vacuum blast oven in step S12 is 60~80℃, and the drying time is 2~4h. The argon protection temperature of the tubular furnace in step S13 is 450~500℃, and the insulation time is 1~3h. The hydrogen reduced in the vacuum tubular sintering furnace is high-purity hydrogen (purity = 99.999%), the reduction temperature is 800~950℃, the heating rate is 5℃ / min, and the reduction time is 6~10h.

[0045] S20: Weigh the components of the Ti(C,N)-based metal ceramic tool material described in Example 1 in various weight ratios, mix the raw materials and perform ball milling to obtain a mixed powder.

[0046] Wherein, the ball-to-material mass ratio of the ball milling treatment in step S20 is 8:1, the ball mill speed is 200 r / min, and the ball milling mixing time is 24 h.

[0047] In this embodiment, the mixing method mainly adopts wet grinding. Therefore, after the step S20 is completed, the obtained mixed powder needs to be dried.

[0048] Before executing step S30, the following steps need to be performed:

[0049] S21: adding paraffin wax to the mixed powder for mixing and granulating the mixture to facilitate cold isostatic pressing.

[0050] S30: cold isostatic pressing the mixed powder to obtain a Ti(C,N)-based metal ceramic blank, and sintering the blank to obtain the machinable high-strength steel Ti(C,N)-based metal ceramic tool material as described in Example 1.

[0051] The pressure of the cold isostatic pressing process in step S30 is 180 MPa, the holding time is 3 min, the sintering temperature in the sintering process is 1430 degrees Celsius, the sintering time is 60 min, and the sintering method used is atmosphere pressure sintering or vacuum sintering.

[0052] In order to test the solution in Example 2, the following test example is also provided:

[0053] Test Example 1

[0054] S11: convert W and La into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and weigh the corresponding mass of ammonium paratungstate and lanthanum nitrate.

[0055] S12: Dissolve ammonium paratungstate and lanthanum nitrate separately with deionized water, and place the dissolved solutions in a magnetic stirrer for stirring and mixing for 24 hours. After sufficient reaction, dry them in a vacuum blower oven at 60° C. for 2 hours to obtain a precursor powder.

[0056] S13: The precursor powder is ground with an agate mortar and kept warm at 450°C for 1 hour in an argon tube furnace to obtain a mixed oxide containing rare earth oxide and tungsten oxide. The oxide is then placed in a vacuum tube sintering furnace for reduction and cooled to room temperature in a hydrogen environment to obtain a W-10wt.%La2O3 composite powder.

[0057] The hydrogen reduced in the vacuum tube sintering furnace is high-purity hydrogen (purity = 99.999%), the reduction temperature is 800°C, the heating rate is 5°C / min, and the reduction time is 6h.

[0058] S20: Weigh raw materials with the following weight ratios, mix the raw materials, and then perform ball milling to obtain a mixed powder:

[0059] 8wt.% TiN; 15wt.% WC; 15wt.% Co; 1wt.% C; 4wt.% Ta; 0.2wt.% W-10wt.% La2O3; 55wt.% TiC.

[0060] The ball-to-material mass ratio of the ball milling treatment is 8:1, the ball mill speed is 200 r / min, and the ball milling mixing time is 24 h.

[0061] After the step S20 is completed, the obtained mixed powder needs to be dried and the step S21 is performed.

[0062] S21: adding paraffin wax to the mixed powder for mixing and granulating the mixture to facilitate cold isostatic pressing.

[0063] S30: performing cold isostatic pressing on the mixed powder to obtain a Ti(C, N)-based metal ceramic blank, and performing atmosphere pressure sintering on the blank to obtain a Ti(C, N)-based metal ceramic tool material.

[0064] The pressure of the cold isostatic pressing process in step S30 is 180 MPa, the holding time is 3 min, the sintering temperature in the sintering process is 1430 degrees Celsius, the sintering time is 60 min, and the argon pressure is 2.5 MPa.

[0065] The following table shows the performance test results of the Ti(C,N) based cermet tool material prepared in Test Example 1:

[0066] performance Numeric Density (%) 99.5 Hardness (HV) 1653.2 Flexural strength (MPa) 1400.9 <![CDATA[Fracture toughness (MPa·m 0.5 ).]]> 13.6

[0067] Metal ceramic tool materials (such as Figure 2) CNC cutting of martensitic stainless steel workpiece with the grade of 0Cr17Ni4Cu4Nb was performed, with a rake angle of -5°, a back angle of 3°, and a cutting speed of 300r / min. Figure 3 As shown in the figure, it can be seen that the iron chips are regularly curled, indicating that the tool has good wear resistance. The workpiece after processing is measured using a three-coordinate measuring machine, and the surface roughness Ra is 4 microns. The workpiece is cut using the metal ceramic tool material prepared by the process in Test Example 1. The cutting line after processing is as shown in the figure. Figure 3 As shown, the workpiece obtained after processing has a better gloss.

[0068] Test Example 2

[0069] Different from Test Example 1, in the weighed raw materials: W-10wt.%La2O3 content is 0.4wt.%, and TiC content is 53wt.%.

[0070] The following table shows the performance test results of the Ti(C,N) based cermet tool material prepared in Test Example 2:

[0071] performance Numeric Density (%) 99.2 Hardness (HV) 1636.4 Flexural strength (MPa) 1450.4 <![CDATA[Fracture toughness (MPa·m 0.5 ).]]> 14.30

[0072] The metal ceramic tool material prepared by the above process was used to perform CNC cutting on a martensitic stainless steel workpiece with a grade of 0Cr17Ni4Cu4Nb, with a front angle of -5°, a back angle of 3°, and a cutting speed of 300r / min. After processing, the iron chips showed regular curling, indicating that the tool had good wear resistance. The workpiece after processing was measured using a three-coordinate measuring machine, and the surface roughness Ra was 6 microns.

[0073] Test Example 3

[0074] The difference from Test Example 1 is that the weighed raw materials include: TiC content of 57wt.%, 0wt.% W-10wt.% La2O3.

[0075] The following table shows the performance test results of the Ti(C,N) based cermet tool material prepared in Test Example 3:

[0076] performance Numeric Density (%) 99.4 Hardness (HV) 1594.7 Flexural strength (MPa) 1376.3 <![CDATA[Fracture toughness (MPa·m 0.5 ).]]> 12.90

[0077] The metal ceramic tool material prepared by the above process was used to perform CNC cutting on a martensitic stainless steel workpiece with a grade of 0Cr17Ni4Cu4Nb, with a rake angle of -5°, a back angle of 3°, and a cutting speed of 300r / min. The workpiece after machining was measured using a three-coordinate measuring machine, and the surface roughness Ra was 20 microns.

[0078] In summary, the internal structure of the composite material obtained by adopting the scheme in Example 2 will be further densified, and while ensuring the hardness, the bending strength and toughness will be higher. The scheme of Example 2 is conducive to ensuring that the structure is uniform and fine, thereby obtaining a composite material with better comprehensive performance. Among them, Test Example 1 is the preferred scheme, and the comprehensive performance of the obtained material is stronger.

[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, but not to limit them. Anyone familiar with the technology can modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. Ti(C,N) based metal ceramic tool material, characterized in that: The composition comprises the following weight ratios: 8wt.% TiN; 15wt.% WC; 15wt.% Co; 1wt.%C; 4wt.%Ta; 0wt.%~4wt.%W-10wt.%La2O3; 53 wt.% to 57 wt.% TiC; The preparation method of the Ti(C,N)-based metal ceramic tool material comprises the following steps: S10: converting W and La into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and weighing the corresponding mass of ammonium paratungstate and lanthanum nitrate for pretreatment to obtain a composite powder of W-10wt.%La2O3; S20: Weighing the components of the Ti(C,N)-based metal ceramic tool material in various weight ratios, mixing the raw materials and then subjecting them to ball milling to obtain a mixed powder; S30: performing cold isostatic pressing on the mixed powder to obtain a Ti(C, N)-based metal ceramic green body, and sintering the green body to obtain a Ti(C, N)-based metal ceramic tool material.

2. The Ti(C,N) based metal ceramic tool material according to claim 1, characterized in that: The particle size of the TiN powder is 0.1 to 2.0 microns, the particle size of the WC powder is 0.1 to 1.56 microns, the particle size of the Co powder is 1.0 to 10.0 microns, the particle size of the C powder is 0.1 to 2.7 microns, the particle size of the Ta powder is 0.1 to 4.5 microns, and the particle size of the TiC powder is 0.1 to 4.5 microns.

3. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 1, characterized in that: The step S10 comprises the following steps: S11: convert W and La into the mass of ammonium paratungstate and lanthanum nitrate in a ratio of 90:10, and weigh the corresponding mass of ammonium paratungstate and lanthanum nitrate; S12: dissolving ammonium paratungstate and lanthanum nitrate respectively in deionized water, placing the dissolved solutions in a magnetic stirrer for stirring and mixing, and drying in a vacuum blower oven after sufficient reaction to obtain a precursor powder; S13: Grind the precursor powder with an agate mortar and keep it warm in an argon tube furnace to obtain a mixed oxide containing rare earth oxide and tungsten oxide, and place the oxide in a vacuum tube sintering furnace for reduction and cool to room temperature in a hydrogen environment to obtain a W-10wt.% La2O3 composite powder.

4. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 3, characterized in that: The drying temperature of the vacuum blast oven in step S12 is 60-80° C., and the drying time is 2-4 hours; In step S13, the argon protection temperature of the tubular furnace is 450-500°C, the insulation time is 1-3h, the hydrogen reduced in the vacuum tubular sintering furnace is high-purity hydrogen, the reduction temperature is 800-950°C, the heating rate is 5°C / min, and the reduction time is 6-10h.

5. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 1, characterized in that: The ball-to-material mass ratio of the ball milling treatment in step S20 is 8:1, the ball mill speed is 200 r / min, and the ball milling mixing time is 24 h.

6. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 5, characterized in that: After the step S20 is completed, the obtained mixed powder is dried.

7. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 1, characterized in that: The pressure of the cold isostatic pressing process in step S30 is 180 MPa, and the holding time is 3 min; The sintering temperature during the sintering process is 1430 degrees Celsius and the sintering time is 60 minutes.

8. The method for preparing the Ti(C,N)-based metal ceramic tool material according to claim 7, characterized in that: The following steps need to be performed before the cold isostatic pressing process: S21: adding paraffin wax to the mixed powder for mixing and granulating the mixture to facilitate cold isostatic pressing.

Citation Information

Patent Citations

  • Ti (C, N) base metal ceramic with homogeneous ring core structure and preparation method thereof

    CN110396632A